3D Power Doppler vascular indices as a novel technique in assessing the outcome of minimally invasive techniques in uterine fibroids treatment - Stępniak, Anna; Czuczwar, Piotr (Menopause Review/Przegląd Menopauzalny, 2017)
Uterine fibroids are considered to be the most frequent female benign tumours. The most common reported symptoms of fibroids are heavy menstrual bleeding and painful menstruation, pelvic pain, urinary problems, constipation, as well as infertility and recurrent pregnancy loss. The mainstay of fibroid treatment is surgery, but nowadays minimally-invasive techniques are growing in popularity. Vascularity of fibroids may play a role in the outcome of these techniques, which is why it is important to find an objective, reproducible technique to measure the vascularization before and after the procedure. The 3D Power Doppler vascular indices (3DPDVI) allow objective assessment of vascularization in the entire volume of the tumour. Initially this technique was mostly used in experimental imaging phantoms, but recently many studies focus on the clinical utility of this technique. Power Doppler allows to obtain information on vascularity in the area of interest, while 3DPDVI can be objectively calculated by the Virtual Organ Computer-aided AnaLysis (VOCAL™) software. 3DPDVI showed high reproducibility in most of the studies. This technique has an important role in monitoring the outcome of minimally invasive procedures in fibroid treatment, because they affect vascularity of the tumours. Although there are some limitations of 3DPDVI, it seems that their application may be an effective tool in objective assessment of vascularity of fibroids. However further studies are required to consolidate the usage of 3DPDVI in clinical practice.